2018
DOI: 10.1007/978-1-4939-7816-8_20
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Ca2+ Signaling Induced by Amyloid–β Oligomers in Aged Hippocampal Neurons In Vitro

Abstract: Alzheimer's disease (AD), the most prevalent dementia linked to aging, involves neurotoxic effects of amyloid β species and dishomeostasis of intracellular Ca. To investigate mechanisms of AD, the effects of soluble species of amyloid β oligomers (Aβo) prepared in medium devoid of glutamate receptor agonists can be tested on intracellular Ca in long-term cultures of rat hippocampal neurons that reflect aging neurons. Furthermore, changes in expression of proteins involved in oligomer responses and AD can be te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Interestingly, this effect of Aβ42 oligomer application was not revealed at the early stages of primary neuronal culture development (2-10 DIV), but Ca 2+ activity was sharply increased beginning at DIV 14, at which point different age-related signs were observed in neurons. In this regard, the cytosolic and mitochondrial Ca 2+ responses induced by single Aβ42 oligomer administration increased dramatically over time (adult cultures DIV 21-28) ( Calvo-Rodríguez et al, 2016 ; Núñez et al, 2018 ). Our data indicated that chronic Aβ42 application increased the suppression of functional Ca 2+ activity in primary hippocampal cultures and may correlate with in vivo studies of Ca 2+ activity, indicating neural dysfunction in the brains of aging mice with modeled AD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this effect of Aβ42 oligomer application was not revealed at the early stages of primary neuronal culture development (2-10 DIV), but Ca 2+ activity was sharply increased beginning at DIV 14, at which point different age-related signs were observed in neurons. In this regard, the cytosolic and mitochondrial Ca 2+ responses induced by single Aβ42 oligomer administration increased dramatically over time (adult cultures DIV 21-28) ( Calvo-Rodríguez et al, 2016 ; Núñez et al, 2018 ). Our data indicated that chronic Aβ42 application increased the suppression of functional Ca 2+ activity in primary hippocampal cultures and may correlate with in vivo studies of Ca 2+ activity, indicating neural dysfunction in the brains of aging mice with modeled AD.…”
Section: Discussionmentioning
confidence: 99%
“…Cell treatments were performed in serum-free RPMI medium for 24 h. The stimuli used were: 100 ng/mL LPS (lipopolysaccharide from E. coli 0111:B4, Sigma-Aldrich, St. Louis, MO, USA); 25 μM paraquat (PQ; Sigma-Aldrich, St. Louis, MO, USA); 20 ng/mL IL-4 + 50 ng/mL IL-13 (PeproTech, Hamburg, Germany); and 1 μM Aβ oligomers (Bachem, Bubendorf, Switzerland). Aβ oligomers were prepared as described by Nuñez et al [ 39 ]. After treatments, cells were collected to analyze membranes and intracellular proteins, while extracellular media were cleaned from detached cells and debris (as indicated below) and stored at −80 °C until processed.…”
Section: Methodsmentioning
confidence: 99%
“…However, preparation of Aβ oligomers constitutes a complex method, and the difficulty to obtain reproducible oligomer preparations between different batches is the main reason for the existence of different protocols (Caballero et al, 2016). Based on the methods described by Núñez and coworkers (Núñez et al, 2018), we designed a new protocol to prepare Aβ oligomers, which is summarized in The tubes were spun in a SpeedVac centrifuge (800g, 10 minutes at RT, less than 25ºC to avoid peptide denaturalization) to remove the HFIP and to get the Aβ peptide as a film. The peptide film was then resuspended in 14.6 μl of DMSO to get Aβ 5 mM.…”
Section: Amyloid β 1-42 (Aβ1-42) Oligomers Preparationmentioning
confidence: 99%